School Climate and the Manifestation of the Core Values Among The Grade 5 Learners: Basis For Enhancing the Teaching of Edukasyon Sa Pagpapakatao (ESP) - Ladaran, Carmena C.; Biol Jr, Isidro M. (RIRAI Publisher, 2025)
This study investigated the relationship between school climate and the manifestation of core values among Grade 5 learners at Jose T. Domingo Sr. Central Elementary School. Utilizing a descriptive-correlational design and grounded in Bandura's Social Cognitive Theory, the research explored the influence of school safety, teaching and learning practices, community relationships, and the school environment on the integration of values like Maka-Diyos, Makatao, Makakalikasan, and Makabansa within Edukasyon sa Pagpapakatao (ESP) instruction. Findings revealed a generally positive school climate, with students demonstrating core values, particularly environmental awareness (Makakalikasan) and patriotism (Makabansa), which were significantly related by the school environment. The study proposed an Integrated Values Development Program to further enhance values education